CONCEPTUAL FOUNDATIONS OF HEALTH-IMPROVING PHYSICAL ACTIVITY IN MODERN SOCIETY - V.Sh. Rakhimov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the conceptual foundations and methodological approaches to organizing health-improving physical activity within modern society. The study focuses on developing a comprehensive health promotion concept based on systematic physical activity, individualized approaches, and the integration of modern monitoring technologies. The results of the pedagogical experiment demonstrate that regular and structured physical activity significantly improves physical fitness indicators, including strength, endurance, flexibility, and functional condition (p<0.05). Furthermore, the implementation of the concept contributes to disease prevention, improved psycho-emotional well-being, and the formation of a sustainable healthy lifestyle across different population groups.